Acoustic emission and microslip precursors to stick‐slip failure in sheared granular material. Issue 21 (4th November 2013) - Johnson, P. A.; Ferdowsi, B.; Kaproth, B. M.; Scuderi, M.; Griffa, M.; Carmeliet, J.; Guyer, R. A.; Le Bas, P‐Y.; Trugman, D. T.; Marone, C.
Abstract [1] We investigate the physics of laboratory earthquake precursors in a biaxial shear configuration. We conduct laboratory experiments at room temperature and humidity in which we shear layers of glass beads under applied normal loads of 2–8 MPa and with shearing rates of 5–10 µm/s. We show that above 3 MPa load, acoustic emission (AE), and shear microfailure (microslip) precursors exhibit an exponential increase in rate of occurrence, culminating in stick‐slip failure. Precursors take place where the material is in a critical state—still modestly dilating, yet while the macroscopic frictional strength is no longer increasing.